HUBUNGAN KEPATUHAN KONSUMSI TABLET FE TERHADAP KEJADIAN ANEMIA PADA IBU HAMIL DI KECAMATAN PATALLASSANG KABUPATEN GOWA TAHUN 2016 - Darmawansyih, Darmawansyih (Alami Journal (Alauddin Islamic Medical) Journal, 2017)
Prevalence of iron deficiency anemia in pregnancy in the world about 35-75 %. The most common causes of anemia in pregnancy is iron deficiency. In Indonesia the rate of anemia in pregnant women was 37.1% and increases with increasing gestational age. To prevent anemia in pregnant women can doing by provision of iron tablets. In Indonesia the provision of iron tablets has been a government program. Although the government has launched the provision of iron tablets, but the rate of anemia among pregnant women is still quite high. In the district Of Gowa, especially in Patallassang the rates of anemia is still high and increased from year to year. This study aimed to examine the association between adherence iron tablet consumption with the incidence of anemia among pregnant women in the district. Pattallassang, Gowa. The type of research is observational analytic research with cross-sectional approach. Of the 57 samples were obtained as much as 86% adherent to drink tablets Fe and 14% non-compliant. Meanwhile there are 93% of respondents who experienced mild anemia, severe anemia 1.8% and 5.3% of respondents had a normal hemoglobin level. By Chi Square test P values obtained for the relationship between the consumption of tablet Fe compliance with the incidence of anemia among pregnant women 0.036 (P <0.05) Conclusion: There is a relationship between the consumption of iron tablet compliance with the incidence of anemia among pregnant women in the district. Patallassang, Gowa.